Does my child have autism? a parent's guide to early detection and intervention in autism spectrum disorders - Stone, Wendy L. (Jossey-Bass, 2006)
The most crucial aspect of treating and helping kids with Autism Spectrum Disorders (ASD) is catching it early and beginning treatment before it's too late. That's why this book answers the question that millions of parents in American today are asking: 'Is my child just having normal developmental problems, behaving oddly, on his own curve, or does he have autism. I know if I find out early enough, we can help more&so please tell me, how do I know?' Autism has become a major concern for millions of parents in America, as what appears to be a mysterious epidemic of a broad spectrum of autistic symptoms has plagued our population, from Asperger's Syndrome, to Pervasive Developmental Disorders, to the more extreme form of Autism portrayed in the film The Rain Man. The latest research has shown that Autism is present from very early in life, with an average onset of 16-20 months in most cases. Yet most children are not diagnosed until much later, when they are three, four or even older, despite the fact that there are is a much greater potential to improve treatment outcomes by providing diagnosis and intervention at an earlier age. Our author is an expert in the field, enjoying international acclaim for having developed the widely used Screening Tool for Autism in Two Year Olds (STAT). She believes that she it is now possible to identify Autism Spectrum Disorder as early as 18 months and hopes that her current research and clinical practice will prove that she can go as young as 12 months. In any case, she is on the cutting edge of research, theory, and practice in early detection and will provide in this book all of the key 'red flags' to watch for, including poor communication, avoiding eye contact, anti-social behaviors, tics and other compulsive routine behavior, failure to form attachments, and many other symptoms. Her book provides specific checklists of symptoms to watch for and a screening test that everyone can use at home. Her evaluation tool, STAT, moreover is interactive so that the best ways to intervene are revealed in the evaluation itself. She will also provide guidelines for early intervention, both at home, in school, and with professional support, including intervention strategies in setting goals to build skills like interactive play, functional play, communication, interaction, and organizing activities and working with home routine